ANALISIS PENGARUH MOTIVASI KERJA,KOMPENSASI, DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI (STUDI KASUS PEGAWAI NEGERI SIPIL DI BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA BATANG) (Students' Journal of Economic and Management, 2015)
This study aims to determine the effect of work motivation, compensation, career and development of the performance of employees. Object of study in this paper is a civil servant in BPPKB Trunk. The sampling technique in this research is using purposive Samplingberjumlah 108 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondent in order to obtain information. The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test realibitas instrument. Test f jointly determine the independent variable on the dependent variable. Determination test conducted determine the ability of independent variables in explaining the dependent variable. To test the effect of partially each independent variable is done by t test.The results showed that job motivation positive and significant impact on employee performance, compensation and significant positive effect on employee performance, career development and a significant positive effect on employee performance. Keywords: work motivation, compensation, career development and employee performance.